A Comparative Study Of Different Intrusion Methods And Their Effect On Maxillary Incisors (Journal of Pharmaceutical Negative Results, 2023)
Introduction: To analyze and contrast the rates of root resorption and intrusion of maxillary incisors produced by Rickett's utility arch, Kalra's Simultaneous Intrusion & Retraction arch, and arch with Reverse Curve of Spee, respectively.Methods: The research was carried out on a total of 30 patients who ranged in age from 14 to 25 years old and had a deep bite that required at least a 2–4 mm intrusion of their maxillary incisors. On the basis of the intrusion method that was employed, these patients were randomly assigned to one of three groups: Rickets utility arch (Group I), K-SIR arch (Group II), or RCS arch (Group III) (Group III). The quantity of root resorption and the amount of incursion that took place throughout the process were both measured for each subject. In order to analyze the skeletal and dental alterations that occurred both before to and after incisor intrusion, seven angular and six linear cephalometric measurements were taken.Results: The real incisor intrusion that could be obtained with a utility arch was 1.6 millimeters on average, whereas with K-SIR it was 1.25 millimeters, and with RCS it was 0.70 millimeters. The difference between the three rates was not statistically significant (p = 0.451); the rate of intrusion of the utility arch was 0.44 mm/month, the K-SIR was 0.33 mm/month, and the RCS was 0.35 mm/month. When compared to the K-SIR value of 1.08 mm and the RCS value of 0.96 mm, the mean root resorption of the utility arch was much greater at 1.56 mm.Conclusion: When compared to the K-SIR arch, the intrusion rate and root resorption are much higher for the utility arch. On the other hand, the root resorption is significantly lower for the K-SIR arch, despite the fact that the rate of intrusion is practically same.